Recyclable and reformable epoxy resins based on dynamic covalent bonds – Present, past, and future - Memon, Hafeezullah; Wei, Yi; Zhu, Chengyan (Polymer testing, 2022)
Epoxy resins, as a typical class of thermosetting polymers, have widespread industrial applications such as adhesives, coatings, electronic encapsulants, and polymer matrices for advanced composites, owing to their excellent mechanical performance, adhesive capacity, dimensional stability, heat, and chemical resistance. However, conventional epoxy resins cannot be reprocessed, repaired, or recycled due to their permanent crosslinked structures, making it a long-standing challenge to process and recycle the ever-increasing epoxy and epoxy-based composite similar to thermoplastics. Therefore, both economic and environmental factors are driving the development of reformable and recyclable epoxy resins. In this paper, various such epoxy vitrimers containing dynamic covalent bonds are reviewed. Future potentials of these epoxy vitrimers are also discussed. •Summarizes recent development in the field of recyclable epoxy based on dynamic covalent bonds.•Suggests potential research subjects as well as potential future application.•Provides a critical discussion on the progress of recyclable and reformable epoxy.